The Role of Digital Financial Literacy in Moderating the Relationship between Digital Payment Usage and Students' Financial Management Behavior - Putri, Ari Pradina (GREENOMIKA, 2025)
The purpose of this study is to evaluate the effect of digital payment systems on student financial management and to examine the function of digital financial literacy as a moderating factor in the connection. The quantitative method employed in this investigation uses a survey technique, which was given to STMIK Pontianak pupils as the population examined. Thirty participants chosen as samples were drawn using a purposive sampling method. A closed questionnaire based Likert scale was used to gather the data, which was next examined using a straightforward linear regression test and moderated regression analysis (MRA) facilitated by IBM SPSS software version 26. The study's findings show that students' financial management is positively and significantly affected by the use of digital payments. Driven by characteristics like automatic recording and direct transaction monitoring, students using digital payment methods more frequently exhibit superior financial management conduct. Put another way, the advantages of utilizing digital payments for pupils' financial conduct apply broadly irrespective of their degree of understanding of digital financial literacy. The results of this study have management ramifications that suggest digital financial service providers and universities can promote the use of digital payment technology as a tool to enhance student financial management.